Regional citrate anticoagulation in hemodialysis: an observational study of safety, efficacy, and effect on calcium balance during routine care. Issue 1 (December 2016) - Singer, Richard; Williams, Oliver; Mercado, Chari; Chen, Bonny; Talaulikar, Girish; Walters, Giles; Roberts, Darren
Abstract Background Regional citrate hemodialysis anticoagulation is used when heparin is contraindicated, but most protocols require large infusions of calcium and frequent intradialytic plasma ionized calcium measurements. Objectives The objective of this study was to determine the safety, efficacy, and effect on calcium balance of regional citrate anticoagulation using sparse plasma ionized calcium sampling. Design The design of this study was observational. Setting The setting of this study was the hospital hemodialysis center. Patients The subjects of this study were the hospital hemodialysis patients. Measurements Dialysate calcium concentration by atomic absorption spectroscopy and total dialysate weight were used as measurements. Methods Regional citrate anticoagulation was introduced using zero calcium dialysate, pre-dialyzer citrate infusion, and post-dialyzer calcium infusion. Infusions were adjusted based on pre- and post-dialyzer calcium measurements obtained at least twice during a 4-h dialysis. The protocol was simplified after the first 357 sessions to dispense with post-dialyzer calcium measurements. Heparin-anticoagulated sessions were performed using acetate-acidified 1.25 mmol/L calcium or citrate-acidified 1.5 mmol/L calcium dialysate. Calcium balance assessment was by complete dialysate recovery. Safety and efficacy were assessed prospectively using a point-of-care database to record ionized calcium and clinical events. Groups were compared usingt test, ANOVA, Wilcoxon rank sum, or Kruskal-Wallis as appropriate. Results Seventy-five patients received regional citrate-anticoagulated dialysis over 1051 dialysis sessions. Of these, 357 dialysis sessions were performed using the original citrate anticoagulation protocol and 694 using the simplified protocol. Dialysis was effective and safe. Only 3 dialyzers clotted; 1 patient suffered symptomatic hypercalcemia and none suffered symptomatic hypocalcemia. Calcium balance was assessed in 15 regional citrate-anticoagulated dialysis sessions and 30 heparin-anticoagulated sessions. The median calcium loss was 0.8 mmol/h dialyzed in both groups (p = 0.43), and end of treatment ionized calcium was the same in both groups (1.07 ± 0.04 mmol/L). Limitations Our findings for calcium balance, efficacy, and safety are valid only for the protocol studied, which excluded patient with severe liver dysfunction. Conclusions Regional citrate dialysis can be performed safely and effectively using a sparse plasma calcium sampling protocol. The calcium balance induced by this protocol is not different to that seen in standard heparin-anticoagulated dialysis, but in the absence of prospective studies, it is unknown whether this is optimal for patient care. ABRÉGÉ Mise en contexte On recommande l'utilisation de l'anticoagulation régionale au citrate (ARC) d'un circuit de dialyse lorsque l'héparine est contre-indiquée. Toutefois la plupart des protocoles requièrent alors une perfusion de calcium et de fréquentes mesures intradialytiques du taux de calcium ionisé plasmatique. Objectifs de l'étude L'étude visait à déterminer l'innocuité l'efficacité et les effets sur l'équilibre calcique de l'ARC à l'aide d'un protocole de prélèvements épars du calcium ionisé plasmatique. Type d'étude et participants Il s'agit d'une étude observationnelle menée sur les patients de centres d'hémodialyse en milieu hospitalier. Méthodologie L'anticoagulation régionale au citrate implique l'utilisation de trois différentes solutions : un dialysat sans calcium une perfusion de calcium pré-dialyseur ou une perfusion de calcium post-dialyseur. Les perfusions avaient été ajustées selon les taux de calcium mesurés au minimum deux fois pré-dialyseur et post-dialyseur, au cours d'une hémodialyse de quatre heures. Après 357 séances, la mesure du taux de calcium post-dialyseur a été éliminée pour simplifier le protocole. Les séances où l'héparine agissait à titre d'anticoagulant ont été effectuées au moyen de deux différents dialysats : une solution à 1, 25 mmol/L de calcium acidifiée à l'acétate et une solution à 1, 5 mmol/L de calcium acidifiée au citrate. Le bilan calcique s'est fait en récupérant la totalité du dialysat. L'innocuité et l'efficacité ont été évaluées de façon prospective en consignant les taux de calcium ionisé et les événements cliniques à l'aide des bases de données du lieu de soins. Les groupes de patients ont été comparés en utilisant le test T, l'ANOVA, le test signé des rangs de Wilcoxon ou le test de Kruskal-Wallis selon le cas. Résultats Au cours de l'étude 75 patients ont reçu des traitements d'hémodialyse sous anticoagulation régionale au citrate, pour un total de 1051 séances analysées. De celles-ci, 357 séances ont été effectuées en suivant le protocole original d'anticoagulation au citrate, alors que 694 l'ont été en suivant le protocole simplifié. La dialyse s'est avérée sécuritaire et efficace : seuls trois dialyseurs ont coagulé, un seul patient a souffert d'hypercalcémie symptomatique et aucun cas d'hypocalcémie symptomatique n'a été rapporté. Le bilan calcique a été évalué lors de 15 séances d'hémodialyse sous anticoagulation par citrate et de 30 séances utilisant l'héparine. La médiane de perte de calcium se situait à 0, 8 mmol/heure de dialyse pour chacun des deux groupes (p = 0, 43) et le taux de calcium ionisé en fin de séance était le même pour les deux groupes (1, 07 ± 0, 04 mmol/L). Limites de l'étude Ces observations de bilan calcique d'efficacité et d'innocuité ne sont valables que pour le protocole utilisé, excluant ainsi les cas de patients souffrant de dysfonction hépatique grave. Conclusions L'anticoagulation régionale au citrate lors de séances d'hémodialyse peut être effectuée à l'aide d'un protocole d'échantillonnage épars du calcium plasmatique. Le bilan calcique établi par ce protocole n'est pas différent de celui observé lors d'une hémodialyse anticoagulée par l'héparine. Toutefois en absence d'études prospectives, nous ignorons si ce protocole est optimal pour prodiguer des soins aux patients.